HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI: SURVEI DI SMAN 1 CIKARANG BARAT - Listiana, Anita; Suharyat, Yayat (Turats, 2016)
This study aims to investigate the relationship between emotional intelligence and students' motivation on the subjects of PAI in SMAN 1 Cikarang Barat. The method used is quantitative survey method with the correlational approach. The population in this study were students of class X SMAN 1 Cikarang Barat numbered 400 students. While the sample in this study were 80 students by random sampling technique. The results showed that there is a positive relationship between emotional intelligence and motivation to learn by regresi ? = ? + bx, then Y = -30.09 + 1.15x and test correlation coefficient of 0.977. This suggests that emotional intelligence contributed 95.45%. The test results significant to the r value obtained for 0977 was significant at the level ? = 0:05 to table the results count r r = 0.977 and r table = 0212, then significant. Thus, it can be concluded that the hypothesis that there is a relationship between emotional intelligence and motivation to learn in SMAN 1 Cikarang Barat "acceptable" and significant. The implication of this study is to improve emotional intelligence and can be done by increasing student motivation on the subjects of PAI in SMAN 1 Cikarang Barat.